Nilai Pendidikan Hindu Pada Kelakon Calon Arang Di Banjar Stya Dharma Desa Basarang Jaya - Megawati Megawati (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2023)
Indonesia is a country that has a variety of tribes, languages, religions, customs and cultures that are all spread throughout the Indonesian archipelago and have their own uniqueness according to their regional origins. Likewise, the island of Kalimantan, especially Central Kalimantan, has its own uniqueness when viewed in terms of culture, language and tradition. But in addition to a well-developed and sustainable local culture, the people of Central Kalimantan also provide space for immigrant communities. One example is the immigrant community from the island of Bali who are Balinese and embrace Hinduism. As a migrant community, Balinese Hindus still maintain the culture and traditions of their origin, namely the island of Bali. One tradition that is still maintained is the performance of the Calon Arang kelakon by the Banjar Stya Dharma group in Basarang Jaya Village. So this performance needs to be studied for its background and the meaning contained in the performance needs to be known. The problem formulation in this research are: 1) What is the meaning of kelakon Calon Arang for the Stya Dharma banjar community in Basarang Jaya Village; 2) How is the function of kelakon Calon Arang in Banjar Stya Dharma in Basarang Jaya Village?; and 3) What educational values are contained in kelakon Calon Arang in Banjar Stya Dharma in Basarang Jaya Village. The results of the research include: 1) The performance of kelakon Calon Arang originated from the belief of the people of Basarang Jaya Village, especially Banjar Stya Dharma, in the manifestation of Ida Sang Hyang Widhi Wase implemented in the form of Sesuhunan Ida Ratu Calon Arang who has magical powers that can provide protection and help for the people of Banjar Stya Dharma expressed through requests. 2) Kelakon Calon Arang has functions as: a) Increasing the srada and bhakti of Hindus; b) Fostering ethical awareness in the community; c) Improving character education among the Hindu younger generation; and d) Strengthening the bond of menyamebarye. And 3) The Hindu educational values contained in the Calon Arang kelakon are: a) Tattwa education value; b) Susila education value; and c) Ceremony education value.